Using educational design research to develop authentic learning for graduate entry nursing students in New Zealand. (February 2021) - Macdiarmid, Rachel; Winnington, Rhona; Cochrane, Thomas; Merrick, Eamon
Abstract: This paper describes using an educational design-based methodology to evaluate authentic learning environments for Graduate Entry Nursing (GEN) students. While developing this new GEN programme in New Zealand, two specific challenges arose: how to design and deliver a condensed and intensive programme that met healthcare sector requirements, while ensuring the content met the needs of the typical GEN student. To meet these challenges the authors used educational design research (EDR) as a reflective and iterative approach to develop and adapt the teaching and learning strategies, content, and delivery. EDR involves four phases: exploration and analysis of the issues, design of a prototype intervention, reflection and evaluation, followed by iterative redesign and re-evaluation; this paper reports on Phase 1 and Phase 2. It is envisaged this paper will provide timely insights for those in the process of developing or refining graduate entry programmes in Australasia. Highlights: Condensed graduate entry nursing (GEN) programmes present pedagogical challenges. Educational design research enables an innovative, pragmatic and responsive approach. Authentic content and adaptable delivery motivate students to be active learners. Findings of this work will provide timely insights for those who develop GEN programmes.